2014
DOI: 10.1007/s00572-014-0621-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Glomus iranicum var. tenuihypharum on soil and Viburnum tinus plants irrigated with treated wastewater under field conditions

Abstract: Currently, irrigation using recycled water is increasing, especially in semiarid environments, but a potential problem of using reclaimed wastewater is its elevated salt levels. The application of arbuscular mycorrhizal fungi (AMF) could be a suitable option to mitigate the negative effects produced by the salinity. In this work, the combined effect of Glomus iranicum var. tenuihypharum and two types of water: Control, C, with EC <0.9 dS m(-1) and reclaimed water (wastewater previously treated in a sewage trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…tenuihypharum) have also been observed on soil and Viburnum tinus irrigated with reclaimed water. Good AMF-soil-plant interactions could make it possible to reuse reclaimed water, particularly when the roots are growing in a saline soil [57].…”
Section: Introductionmentioning
confidence: 99%
“…tenuihypharum) have also been observed on soil and Viburnum tinus irrigated with reclaimed water. Good AMF-soil-plant interactions could make it possible to reuse reclaimed water, particularly when the roots are growing in a saline soil [57].…”
Section: Introductionmentioning
confidence: 99%
“…The poor nutritional status of soybean rhizosphere soil also inhibited the growth of the soybean root system, eventually resulting in the poor plant growth and a reduction in yield and quality. After F. mosseae inoculation, soybean biomass increased in the treatment group, showing that by infecting the soybean roots, F. mosseae can enhance the ability of soybean roots to absorb mineral nutrition and moisture through the formation of mycorrhizal structures such as arbuscules and vesicles [22,33,39]. We also found that the physicochemical indexes of rhizosphere soil were significantly higher than those in the control group, suggesting that F. mosseae can improve the rhizosphere microenvironment in continuously cropped soybean under potted-experiments, providing an experimental basis for applying AMF to reduce the incidence of soybean root rot in continuous cropping systems.…”
Section: Discussionmentioning
confidence: 99%
“…AMF establish a symbiotic relationship with terrestrial tracheophyte root systems to promote the absorption of water and minerals (mainly P, but also N, K, Zn, and Mn) [14,15], accelerate the formation of chloroplasts, and improve the photosynthesis rate and plant biomass [16,17]. AMF can play a role in the regulation of the plant defense response through its effect on plant metabolism and the expression of defense-related genes [18,19], improving resistance to diseases, pests, drought [20], and heavy metal pollution [21,22], as well as in maintaining soil ecosystem diversity and microecosystem stability.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors claim that the decrease in leaf Na + content could be partially due to a dilution effect, through an increase in dry matter accumulation [49]. AMF can reduce Cland Na + content and enhance beneficial nutrients, such as P, N, K + , Ca 2+ and Mg 2+ in different plants, such as citrus, wheat and ornamental plants [37,48,50], which consequently increase the K + /Na + , Mg 2+ /Na + , Ca 2+ /Na + and K + /N ratios [30,51]. Improved plant nutrition by AMF symbiosis allows cells to regulate flowing ions more efficiently, enhancing nutrient uptake by transport or availability through mycorrhizal hyphae, conducive to improve salt resistance of mycorrhizal plants.…”
Section: Arbuscular Mycorrhizal Fungi (Amf)mentioning
confidence: 99%
“…On the other hand, some authors reported adverse effects of AMF when plants are fertilized [56,57]. Some recent studies have been focused on the feasibility of using reclaimed municipal wastewater from WWTP (as an alternative water resources) together with AMF inoculation [50,58,59]. In addition to high levels of Na + and Cl -, and depending on its source and treatment, reclaimed wastewater may contain high levels of beneficial elements, such as P, K + , Ca 2+ and Mg 2+ , which can alter AMF function [58].…”
Section: Arbuscular Mycorrhizal Fungi (Amf)mentioning
confidence: 99%